Relationship between human factors and Service Level Agreement usage for health care system - Rozami, Mohammad Nasrollah (2019)
Service Level Agreement (SLA) is a contract between service provider and service recipient, where each service is formally defined. From the SLA management, the service recipient will know what service they will be receive. Most commonly, the parameter of SLA defines QoS (Quality of Service) to give overall performance of a service including the response time, throughput, access time, delay or user complain. The issue such as system failure, service unavailability, technical problem or hardware inaccessibility are examples of problems occurred in service platforms. The issue is normally covered in SLA which explain in detail in terms of official agreement. Managing SLA can become difficult as it normally depends on human interference such as user complaints, service violation reports and delays response or action from technical personal. Each violation can be caused by the system or human when delivering the service. Also, the lack of providing the opportunities to staffs to learn and develop new skills become one of the barriers to delivering a good quality of service. The human factor is one of the problems need to be considered very well in a hope the quality of the service can meet the satisfaction of the user. The objective of this research is to study the important human factor that influence SLA usage and further proposed an SLA enforcement model with accentuation of these human factors. This research consists of three phases. The first phase is defining the research design and identify the human factor based on study previous researches papers. There are four human factors used in this research as suggested by most paper reviewed. There are user willingness, skill or knowledge, info sharing and IT staff adequacy. The second phase consist of instrument plan, population and sample research, data collection technique, data analysis method, pilot study and theoretical study. The survey form distributed focused on the two type of groups studied which are service provider and service recipient of healthcare information system. The third phase of this research is developing the model and rules to measure the SLA usage level in domain specific information system. The Pearson test analysis is used to analyse the level of four element of human factor which can give influence on the SLA usage. The level of impact on SLA usage show differences based on indicated level of human factor. It can be concluded that, there is a positive correlation between human factor (user willingness, skill/knowledge, information sharing, IT staff adequacy) with SLA usage. The model development was used for this research to find the correlation between human factor and service level agreement usage. Although the result of the Pearson correlation analysis was at moderate positive correlation, the human factor needs to be considered when delivering services. It is important to enforce SLA between both service provider and consumer. This will help to minimize the SLA violation and increase the quality of services.